Protection layer-assisted cross-sectional observation method for micro-processed polymer optical fibers - Ryo NAKASHIMA; Takuto NAKANISHI; Keito ISHIDA; Cheng-Yao LO; Heeyoung LEE; Yousuke MIZUNO; Daisuke YAMANE (Mechanical Engineering Journal)
Polymer optical fibers (POFs) are promising candidates for sensor applications due to their high strain resistance, flexibility, and cost-effectiveness. The performance of POF-based sensors can be enhanced through precise micro-processing of the fibers. However, conventional methods for observing POF cross-sections often fail to capture the detailed profiles of micro-processed POFs, leading to inaccuracies in sensor design and analysis. In this work, we developed a new protection layer-assisted cross-sectional observation method to preserve the surface profiles of POFs during cutting and polishing. As a proof of concept, we applied this method to perfluorinated (PF)-POFs dry-etched by reactive ion etching (RIE). Epoxy resin was used as a protection layer to maintain the structural integrity of the fibers during the cutting process. The cross-sectional profiles of the micro-processed PF-POFs were successfully captured using a laser microscope. These profiles, previously difficult to predict, were found to be crucial for analyzing the strain sensor performance. Finite element method simulations further demonstrated the impact of these geometric features on the strain characteristics of the PF-POFs. Our results confirm that the proposed method is effective for constructing accurate design and analysis models of micro-processed POFs, paving the way for improved sensor technologies.